Hemodinâmica, hemogasometria e temperatura de cadelas submetidas a ovariectomia videolaparoscópica sob pneumoperitônio aquecido - Coradini, Gabriela Pesamosca (2019)
The objectives of the study were to verify the changes caused by hemodynamics, hemogasometry, temperature and possible renal lesions in bitches submitted to videolaparoscopic ovariectomy using heated and unheated pneumoperitoneum. They were analyzed 40 bitches, weighing between 15 kg and 20 kg, aged between one and three years, healthy, divided into two groups according to the pneumoperitoneum used: unheated group (GNA) and heated group (GN). The ovariectomy was performed using the two portals technique and maintained in a pneumoperitoneum with a pressure of 12 mmHg. The patients were maintained under inhalational anesthesia and controlled ventilation. The following parameters were measured: heart rate (HR), respiratory rate (f), partial carbon dioxide pressure at end of expiration (EtCO2), arterial oxygen partial pressure (PaO2), partial arterial carbon dioxide pressure (PCO2), peripheral saturation of oxyhemoglobin (SpO2), sodium bicarbonate (HCO3-), systolic (SBP), mean (MAP) and diastolic (DBP) pressures, cardiac output (CO) and temperatures. They were collected samples of arterial blood and urine for evaluations. The HR increased at the beginning of the pneumoperitoneum in GNA, however DC and the pressures did not present any relevant difference between the two groups. There was an increase in ETCO2 in both groups, but f remained constant. PaO2 and PaCO2 had a two-fold increase in both groups. The pH presented a decrease at the same time that PaCO2 increased, characterizing acute respiratory acidosis. HCO3- presented difference in T7 in GNA. At the temperatures there was no difference as well as in renal parameters. The present study provides important information regarding the use of the two modalities of pneumoperitoneum used, demonstrating that there were no significant differences between groups using heated and unheated pneumoperitoneum, both dry for the surgery studied under the reported anesthetic conditions. The patients demonstrated anesthesia stability, no hypothermia or hemodynamic changes beyond those expected according to the parameters evaluated and conditions under study. Despite the results obtained, it is necessary to continue the study line comparing these modalities evaluated with other modes of pneumoperitoneum, such as humidified, in dogs.